2012
DOI: 10.1002/clc.21964
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relation of Total Serum Bilirubin to Coronary Artery Calcification Score Detected by Multidetector Computed Tomography in Males

Abstract: Background:Serum total bilirubin has been suggested to have potential anti‐inflammatory and antioxidant effects on the vasculature, acting against plaque formation and subsequent atherosclerosis. This study was designed to assess the association of serum total bilirubin with coronary artery calcification (CAC).Hypothesis:Individuals with higher bilirubin level would be less likely to develop CAC.Methods:Male subjects (N = 3408) underwent evaluation of CAC by cardiac computed tomography. Correlation and logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…A supporting study showed an inverse relationship between total serum bilirubin and CAC score in healthy men. For example, an increase of 0.1 mg/dl bilirubin concentration was associated with reduced odds of patients having a CAC score of Ն100 by 29.2% (198). Furthermore, the CAC score was lowered in subjects with elevated bilirubin concentrations and was inversely associated with bilirubin concentrations (158).…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 95%
“…A supporting study showed an inverse relationship between total serum bilirubin and CAC score in healthy men. For example, an increase of 0.1 mg/dl bilirubin concentration was associated with reduced odds of patients having a CAC score of Ն100 by 29.2% (198). Furthermore, the CAC score was lowered in subjects with elevated bilirubin concentrations and was inversely associated with bilirubin concentrations (158).…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 95%
“…Treatment with biliverdin decreased intragraft leukocyte infiltration and inhibited T cell proliferation [128]. Bilirubin protects grafts against nonspecific inflammation-induced injury in syngeneic intraportal islet transplantation in rat model [129]. Injection of bilirubin in mice islet allografts led to generation of T-regulatory cells (Treg cells), suggesting that bilirubin administration leads to graft tolerance by Treg cell generation [130].…”
Section: Role Of Bilirubin In Organ Transplantationmentioning
confidence: 98%
“…30 TB has also been shown to be negatively correlated with arterial stiffness in men with established CHD, 31 and it has been suggested that lower TB is associated with increased risk of coronary artery calcium (CAC). 32,33 In 2012, further evidence for a beneficial role of TB in protecting against CVD events was provided by a large UK primary care-based study. After conventional risk factors were accounted for, the regression models predicted that, compared with patients with a TB level of 0.70 mg/dL, those with a similar CVD risk profile, but a TB level of only 0.35 mg/dL had an 18% higher risk of any CVD event, a 34% higher risk of myocardial infarction, and a 33% higher risk of death resulting from any cause.…”
Section: Associations Between Bilirubin and Cvd Riskmentioning
confidence: 99%